UNA APROXIMACIÓN EPISTEMOLOGICA, DIDÁCTICA Y COGNITIVA A NOCIONES BÁSICAS Y CONCEPTOS DEL CÁLCULO - García O, Gloria; Serrano, Celly; Díaz, Hernán (Tecné, Episteme y Didaxis: TED, 1999)
This article presents the une of investigation “An epistemological didactic and cognitive approximation to the basic motions of Calculus”, of the Master’s program in Mathematics Education. A revision of the tendencies and problems, with respect to the teaching of Calculus and about the cognitive aspects of investigations already completed is presented. A synthesis of the concepts and theories that support the framework of this line of investigation is given.